DEFINITION csubt_refl()
TYPE =
∀g:G.∀c:C.(csubt g c c)
BODY =
assume g: G
assume c: C
we proceed by induction on c to prove csubt g c c
case CSort : n:nat ⇒
the thesis becomes csubt g (CSort n) (CSort n)
by (csubt_sort . .)
csubt g (CSort n) (CSort n)
case CHead : c0:C k:K t:T ⇒
the thesis becomes csubt g (CHead c0 k t) (CHead c0 k t)
(H) by induction hypothesis we know csubt g c0 c0
by (csubt_head . . . H . .)
csubt g (CHead c0 k t) (CHead c0 k t)
we proved csubt g c c
we proved ∀g:G.∀c:C.(csubt g c c)